Bacteriome Diversity of Soil Islands Associated With Bromeliads From Ironstone Outcrops in the Brazilian Pantanal - Fernanda M. R. Godoy; Gecele M. Paggi; Aline P. Lorenz; Jeferson V. Ramos; Daniel G. Franco; Fernando M. L. Calarge; Nayara F. L. Garcia; Marcus V. S. Urquiza; Jolimar A. Schiavo; Nalvo F. Almeida; Marivaine S. Brasil (International Journal of Microbiology)
Knowledge about the diversity and distribution of microorganisms in natural environments is essential for understanding the dominant microbial groups and predicting their ecological functions. This study is aimed at describing the bacteriome diversity in soils associated with bromeliads in the Brazilian Pantanal region, utilizing genomic approaches. We analyzed the 16S rRNA gene from soil environmental DNA (eDNA) samples linked to Bromelia balansae and Deuterocohnia meziana (Bromeliaceae), which inhabit ironstone outcrops in the Pantanal. The analysis revealed Ktedonobacteraceae as the most abundant bacterial group, showing a mean relative abundance of 22.8%±15.5% in B. balansae and 33.5%±18.4% in D. meziana soils. Other highly abundant families were Chthoniobacteraceae and Pyrinomonadaceae, each exceeding 14.5% mean abundance. Despite the similarities in bacteriome composition between the bromeliads, beta-diversity analysis revealed phylogenetic distinctions across localities. The São João and Vale do Paraíso Farms, which experience the highest human impact from livestock farming, showed considerable differences, with 25 and 13 exclusive taxa, respectively. The environmental stresses of ironstone outcrops, such as high insolation and thermal variation, likely favor specific taxa adapted to these conditions. Understanding the bacteriome diversity in these unique habitats is crucial for promoting sustainable use and conserving the Pantanal’s biodiversity.